Probing the Inert Doublet Model via vector-boson fusion at a muon collider - Johannes Braathen; Martin Gabelmann; Tania Robens; Panagiotis Stylianou (Journal of High Energy Physics)
Abstract In this work, we explore the discovery potential of the Inert Doublet Model (IDM) via the vector boson fusion (VBF) channel at a muon collider with centre-of-mass energy of 10 TeV. The Inert Doublet Model is a two-Higgs-doublet model variant with an unbroken discrete ℤ 2 symmetry, featuring new stable scalar particles that can serve as dark matter candidates. Current dark matter data constrain the phenomenologically viable parameter space of the IDM and render certain collider signatures elusive due to tiny couplings. However, VBF-type processes can still exhibit significant enhancements compared to the Standard Model, presenting a promising avenue to probe the IDM at a high-energy muon collider. We consider as our specific target process μ + μ − → ν μ ν ¯ μ AA → ν μ ν ¯ μ jj ll HH $$ μ^{+}{μ}^{-}→ ν_{μ }{\overline{ν}}_{μ } AA→ ν_{μ }{\overline{ν}}_{μ } jj\mathcal{ll} HH $$ , where H and A are the lightest and second-lightest new scalars and ℓ can be electrons or muons. We perform both cut-based and machine-learning improved sensitivity analyses for such a signal, finding a population of promising benchmark scenarios. We additionally investigate the impact of the collider energy by comparing sensitivities to the target process at 3 TeV and 10 TeV. Our results provide a clear motivation for a muon collider design capable of reaching a 10 TeV centre-of-mass energy. We furthermore discuss constraints stemming from new-physics corrections to the Higgs to di-photon decay rate as well as the trilinear Higgs coupling in detail, using state-of-the-art higher-order calculations.